Rearticulating post-pandemic borders - Stojanović, Đorđe (Sociološki pregled, 2022)
This paper theoretically examines the transformation in understanding borders within the COVID-19 (post-)pandemic context. The first part of the paper analyses the immunitary discourse as a new form of governance and interpretation of the “coronocratic” state. The second part explores the advantage of the dynamic/kinetic over static interpretation of boundaries and the importance of their hybrid and polymorphic attributes in the transition to the post-Westphalian international order. In the final part, it considers the implications of the pandemic metanarrative under which COVID-19 is treated as a dominant external threat, a specific type of enemy. Finally, the paper is concluded by identifying a two-fold process in their perception. This process, on the one hand, includes the reduction of the kinetic potentials of borders and, on the other, their externalization to the territories of allochthonous/“third” countries.
Keywords: boundaries; post-pandemic boundaries; state; “coronocracy“; COVID-19